Akuntabilitas dan Transparansi Pengadaan Kapal Nelayan Pada Program Pengelolaan Perikanan Tangkap Di Kementerian Kelautan dan Perikanan - Suyanti, Suyanti; Hernawati, Erna; Subur, Subur (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. This research is an interpretive ethnometodology qualitative study which aims to determine the accountability and transparency of the procurement of fishing boats from the beginning of the procurement intended for community assistance and conformity to government procurement regulations. Accountability refers to the process of procuring fishing boats that have described responsibility for the management of APBN funds, while the transparency referred to is information disclosure to the public as a contributor to the state budget. Accountability and transparency can be realized if they comply with procedures and the existence of independent parties involved. The regulation in question is PP Nomor 16 Tahun 2018 concerning Government Procurement of Goods / Services and Government PP 27 Tahun 2014 concerning Management of BMN. The data sources used were interviews, observations and the presence of supporting documents such as the Berita Acara Serah Terima (BAST). The results of this study indicate that accountability and transparency have mostly been implemented and are in accordance with PP No. 16 Tahun 2018 and PP No. 27 Tahun 2014, however, the constraints of a lack of accountability occur from the external Ministry of Maritime Affairs and Fisheries. Realization of fisheries facilities assistance is not fully in accordance with the target, because there are still recipients who deliberately misuse their use. Keywords. Accountability, PP No. 16 Tahun 2018, PP No. 27 Tahun 2014, Procurement of Fishing Vessels, Transparency. Abstrak. Penelitian ini merupakan penelitian kualitatif etnometodologi interpretif yang bertujuan untuk mengetahui akuntabilitas dan transparansi pelaksanaan pengadaan kapal nelayan yang dari awal pengadaannya diniatkan untuk bantuan masyarakat dan kesesuaian terhadap peraturan pengadaan barang/jasa pemerintah. Akuntabilitas yang dimaksud adalah proses pelaksanaan pengadaan kapal nelayan telah menggambarkan tanggungjawab atas pengelolaan dana APBN, sementara transparansi yang dimaksud adalah keterbukaan informasi kepada masyarkat sebagai penyumbang APBN . Akuntabilitas dan transparansi dapat terealisasi jika mematuhi prosedur dan adanya pihak independen yang terlibat. Peraturan yang dimaksud adalah PP Nomor 16 Tahun 2018 Tentang Pengadaan Barang/Jasa Pemerintah dan PP Nomor 27 Tahun 2014 Tentang Pengelolaan BMN. Sumber data yang digunakan adalah wawancara, observasi dan adanya dokumen pendukung seperti Berita Acara Serah Terima (BAST). Hasil penelitian ini menunjukkan bahwa akuntabilitas dan transparansi sebagian besar telah diterapkan dan telah sesuai dengan PP Nomor 16 Tahun 2018 dan PP Nomor 27 Tahun 2014, namun, kendala dari kurangnya akuntabilitas terjadi dari pihak eksternal Kementerian Kelautan dan Perikanan. Realisasi bantuan sarana perikanan belum sepenuhnya sesuai dengan sasaran, karena masih terdapat penerima yang sengaja menyalahgunakan pemanfaatannya. Kata kunci. Akuntabilitas, PP No 16 Tahun 2018, PP No 27 Tahun 2014, Kapal Nelayan, Transparansi.